PERKEMBANGAN USUS HALUS DAN PERTUMBUHAN AYAM KAMPUNG SUPER YANG DIBERI SINBIOTIK PADA PAKAN YANG DITURUNKAN KANDUNGAN PROTEINNYA: SMALL INTESTINE DEVELOPMENT AND GROWTH OF SUPER NATIVE CHICKENS WITH SYNBIOTICS IN THE FEED WITH REDUCED PROTEIN CONTENT - Imam, Shokhirul; Suryadi, Ujang; Hertamawati, Rosa Tri; Haqqi, Faris Muizzul (Universitas Boyolali, 2024)
The study aimed to determine the development of the small intestine and the growth of super native chickens given synbiotics in the feed with reduced protein content. The research was conducted from June to August 2023. The research design used was a completely randomised design (CRD) with 4 treatments and 5 replicates, each treatment unit contained 10 super native chickens. The synbiotic consists of fermented snail as probiotic and groundnut shell extract as prebiotic. Feed using selfmix with reduced protein content. Synbiotic supplementation in feed consisted of P0 (control), P1 (5 ml/kg), P2 (10 ml/kg), P3 (15 ml/kg). The parameters observed were the weight and length of the small intestine including duodenum, jejenum, and ileum, as well as the final body weight. Data from the study were analysed using Analysis of Variance (ANOVA), if there was an effect of treatment (P < 0.05) followed by honest real difference test. The results showed that the treatment had a significant effect (P <0.05) on duodenum weight and final body weight but had no effect (P>0.05) on jejenum, ileum, or duodenum, jejenum, and ileum length. The conclusion of the study is that synbiotics can increase duodenal weight at the level of 10 ml/kg and final body weight at the level of 5 ml/kg can compensate for the control treatment. Keywords: super native chickens, synbiotics, small intestine, final body weight